Optimization of Creative Industry Technology through E-Store Development in the MSME Business in the Fashion Sector - Citra, Puspa; Erniyati; Harsani, Prihastuti; Suhendar, Endang (Jurnal Pengabdian Masyarakat Inovatif, 2023)
Micro Small Medium Enterprises (MSMEs) are the most important pillar of the Indonesian economy. However, with the pandemic in recent years, MSMEs have experienced an impact, namely in their marketing. With increased internet traffic, they have experienced a shift in the consumption pattern of goods and services from offline to online. In efforts to improve or deal with the impact of a pandemic, every MSME must be able to apply technology-based creative industries. Technology-based creative industries are creative industries that do not only rely on manual creativity but include the use of information technology and computers. Currently, technology-based creative industries play an important role in optimizing marketing strategies. One of the SMEs that is growing rapidly is the fashion sector. This research aims to create a web-based application to increase the added value of the MSME economy. Developing this application design involves making applications, trials, outreach, implementation, and evaluation. To know the function level of the observed application, a questionnaire containing aspects of Usefulness, Statistics, Ease of Learning, and Ease of Use was distributed. The average result is 83%, so the application is very feasible.